ANALISIS MOTIVASI BETERNAK SAPI POTONG BAGI PETERNAK LOKAL DAN TRANSMIGRAN SERTA PENGARUHNYA TERHADAP PENDAPATAN DI KECAMATAN KAIRATU, KABUPATEN SERAM BAGIAN BARAT - Christian Manase Luanmase; Sudi Nurtini; F. Trisakti Haryadi (Faculty of Animal Science, Universitas Gadjah Mada, 2011)
The study was conducted in Kairatu District, Seram Bagian Barat Regency district from July to September 2008. Materials used in this study were 96 respondents of local and transmigrant cattle beef farmers with questionnaires. The samples were drawn from 4 villages, consisting of 2 villages of local peoples and 2 villages of transmigrants using purposive sampling technique, while the 97 respondents consisted of 49 local and 47 transmigrant beef cattle farmers who were drawn using convenience sampling technique. The objectives of the study: 1) to find out the difference in the motivation and the characteristics of the local and the transmigrant farmers, 2) to investigate the impact of characteristics of the local and the transmigrant farmers on their motivation, 3) to investigate the impact of the characteristics of the local and the transmigrant farmers on their income, and 4) to investigate the correlation between breeding motivation and income. The variables measured in this study were breeding motivation, farmerscharacteristics and income. The data were collected and analyzed using software SPSS 17 to measure the breeding motivation level, the farmers’ characteristics and income. The results showed that the significant differences of characteristics between the local and the transmigrant farmers were age (P<0.01), education level (P<0.01), the braveness in risk taking (P<0.10), and working hours (P<0.05). The characteristics that had significant impact on the motivation were farming experience (P<0.05), number of dependants (P<0.05), width of agricultural land (P<0.10), and farmers’ dummy (P<0.01). The characteristics that had significant impact on income were age (P<0.05), educationlevel (P<0.05), farming experience (P<0.10), cattle beef ownership (P<0.05), and farmers’s dummy (P<0.05). The motivation of transmigrant farmers have positive relations to the income (P<0.10).(Key words: Breeding motivation, Farmers characteristics, Local farmers, Transmigrant farmers, Economic motif, Non-economic motif, Income)